Unimodal & kinaesthetic learning styles Predominate in Both Science and Non-Science University Students in Malaysia using VARK / Ai-Hong Chen, Siti Nur Widad Mohd Salaomi, and Ainin Nazrin Ahmad Nazri - Chen, Ai-Hong; Mohd Salaomi, Siti Nur Widad; Ahmad Nazri, Ainin Nazrin (UiTM Cawangan Negeri Sembilan, 2022)
Learning styles play an imperative role in the tertiary education. Several studies have documented that multimodal is dominant in learning styles among university students. Some denote unimodal learning style trends among basic science and non-science students. Dissimilar investigation tools in previous studies complicate the comparison to reach a firm conclusion. We aim to compare the learning styles between science and non-science tertiary learning in Malaysia. This survey was conducted in May-June 2021 after ethical approval. Subjects were recruited using convenient sampling from higher education institutions. The learning styles were investigated using a validated VARK questionnaire. Informed consent was obtained from 148 university students (117 science and 31 non-sciences) before participation. Approximately 82% of the learning style are unimodal. There is no significant difference in learning styles between science and non-science students (Mann Whitney = 1505.50, p>0.05). Kinaesthetic learning styles are predominant (62.8%%). The unimodal findings match those observed in early studies among non-science students but do not support the previous multimodal reports among science students. This discrepancy may be attributed to the imbalanced gender proportion and composition of millennial students. The most visible finding from this study is the predominant unimodal and kinaesthetic learning style among university students in Malaysia in both science and non-science disciplines. Future research may include a more significant male sample size and multiple investigation tools of diverse learning styles classifications to have a wide-ranging understanding of learning styles to strategise pedagogy teaching.